Structural, Spectroscopic, Thermal and Morphological Evaluation of Biogenic ZnO/Ag Nanocomposite using Moringa oleifera Seed Extract for Enhanced Antimicrobial Efficacy - Reena Francy Biju; Jaffrin G; Jobisha J; Matharasi A; Surya Prabha A; Vinisha V; Mary Linet J; Arul Martin Mani J (Chemical Physics Impact, 2025)
In this study, an eco-friendly plant-mediated synthesis method was used to prepare ZnO/Ag nanocomposite with the aid of miracle tree (Moringa oleifera) seeds for potential biomedical applications. The crystalline nature and structural properties of the prepared nanocomposite were determined using X-ray diffraction (XRD), revealing the hexagonal and cubic phases of ZnO and Ag respectively, with the average crystallite size of 23 nm by the Scherrer method. The strain-induced size was also evaluated using the Williamsom-Hall method. Fourier Transform Infrared (FT-IR) spectroscopy confirmed the presence of functional groups while UV–Visible spectroscopy revealed the characteristic absorption bands of the ZnO and Ag in the prepared nanocomposite alongside disclosing the bandgap to be 2.91eV. Optical parameters including Urbach energy and refractive index were examined indicating promising optical application. XPS Analysis provides both qualitative and quantitative insights into the chemical composition and electronic states, offering a comprehensive understanding of the composite's surface characteristics. Thermogravimetric Analysis (TGA) of the as-prepared nanocomposite provided insights into the thermodynamic stability, evincing the activation energy to be 18.39 kJ mol−1. Furthermore, the thermodynamic parameters like Enthalpy, Entropy and Gibbs free energy were also evaluated. Field Emission Scanning Electron Microscopy (FE-SEM) with EDAX, Transmission Electron Microscopy (TEM) and High-Resolution Transmission Electron Microscopy (HR-TEM) with SAED analysis furnished information about the morphology, particle size distribution and chemical composition of the synthesized nanocomposite. The as-prepared biogenic nanocomposite was tested for antimicrobial activity. The synergistic effect of phyto-synthesized metal oxide and noble metal as a nanocomposite with enhanced antibacterial and antifungal potency against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Bacillus cereus, and Aspergillus niger, highlights its potential applications in antimicrobial coating and biomedical field.